Estratégias e modelos de avaliação utilizados pelos Centros de Recursos TIC no aconselhamento de produtos de apoio para alunos com Necessidades Educativas Especiais - Simone da Fonte Ferreira; Ana Margarida Almeida (Universidade do Minho, 2015)
In 2007, the Portuguese Ministry of Education established a network of 25 Centers of ICT Resources for Special Education (CRTIC). These centers, among other missions, are responsible for the assessment of students with Special Educational Needs (SEN) towards the implementation of assistive technologies. In this paper we present the main findings of a study developed under this context, which aimed to understand the practices currently underway in these Centers, particularly in what concerns the strategies and models used in the assessments of students with SEN for assistive technologies use. The study was based on a multi-methodological paradigm as we analyzed data obtained by a questionnaire applied to all the centers, as well as their activity reports and some interviews. Sustained by the practices described and analyzed, we have conceptualized and prototyped a proposal for a support platform, called " Rede NEE " [SEN Network], which includes strategies that may facilitate the monitoring of the assigned assistive technologies.